Multifrequency tympanometry in infants - de Moraes, Tamyne Ferreira Duarte; Macedo, Camila de Cássia; Feniman, Mariza Ribeiro (International Archives of Otorhinolaryngology, 2012)
Introduction: The use of conventional tympanometry is not sufficiently sensitive to detect all cases of middle ear changes, and this hinders accurate diagnosis.Objective: To characterize acoustic immittance measures of infants from 0 to 3 months of age using multifrequency tympanometry in a prospective study.Method: 54 infants from 0 to 3 months of age were evaluated. The inclusion criteria included absence of respiratory infections during the evaluation, presence of transient evoked otoacoustic emissions, and absence of risk indicators for hearing loss. The subjects were evaluated by an audiologic interview, a visual inspection of the ear canal, and measures of acoustic immittance at the frequencies of 226 Hz, 678 Hz, and 1,000 Hz. Tympanometric records of the occlusion effect, tympanometric curve type, tympanometric peak pressure, equivalent ear canal volume, and peak compensated static acoustic admittance were collected.Results: The results indicated the presence of an occlusion effect (2.88% at 226 Hz, 4.81% at 678 Hz and 3.85% at 1,000 Hz), predominance of a tympanometric curve with a single peak (65.35% at 226 Hz, 81.82% at 678 Hz, and 77.00% at 1,000 Hz), and tympanometric peak pressure ranging from -155 to 180 daPa. Further, the equivalent ear canal volume increased with the frequency of the probe (0.64 mL at 226 Hz, 1.63 mho at 678 Hz, and 2.59 mmho at 1,000 Hz) and the peak compensated static acoustic admittance values increased with an increase in frequency (0.51 mL at 226 Hz, 0.55 mmho at 678 Hz and 1.20 mmho at 1,000 Hz). 93.06% of the tympanograms were classified as normal at 226 Hz, 81.82% at 678 Hz, and 77.00 % at 1,000 Hz, respectively.Conclusion: Taken together, these results demonstrated that utilizing these evaluations made it possible to characterize the acoustic immittance measures of infants.
Keywords: hearing; infant; middle ear; acoustic impedance tests